Teknik Pembesaran Kakap Putih (Lates calcarifer) Menggunakan Keramba Jaring Apung (KJA) Kotak di Balai Besar Riset Budidaya Laut dan Penyuluhan Perikanan Gondol, Bali - Azahra, Firdaus V.; Setia, Wibawa G.; Prabowo, Rahardjo S.S. (AKULTURASI, 2025)
Abstract The cultivation of barramundi (Lates calcarifer) is one of the freshwater aquaculture businesses with promising potential for development, with a selling price reaching Rp 75,000 per kilogram. According to demand data from the Ministry of Marine Affairs and Fisheries of Indonesia in 2020, the demand reached 522,267 tons, while production was only 492,267 tons. The higher demand compared to production indicates that barramundi has significant potential for further development. A popular marine cultivation method is the use of floating net cages (FNC). The objective of this research is to analyze the technique of barramundi grow-out (Lates calcarifer) using box-shaped FNCs at the Gondol Marine Aquaculture Research and Fisheries Extension Center (BBRBLPP) in Bali. The data collection techniques used during the internship were both primary and secondary. Activities conducted in the barramundi grow-out process using box-shaped FNCs included pond preparation, seed stocking, feed management, water quality management, fish health management, as well as harvesting and post-harvest activities. A total of 20,900 barramundi seeds were stocked in the box-shaped FNCs at BBRBLPP Gondol. There are two types of box-shaped FNCs at BBRBLPP Gondol: wooden FNCs and HDPE (High-Density Polyethylene) FNCs. The dimensions of the box-shaped FNCs are divided into four sizes: 2x2x2 meters, 3x3x3 meters, 4x4x4 meters, and 2x4x4 meters. The productivity of barramundi grow-out over 30 days yielded an SGR (Specific Growth Rate) of 0,83%. SR (Survival Rate) of 92,1%; 96,2% and 98,9%; and FCR (Feed Conversion Ratio) of 0.654. The total production at the end of the rearing period was 573,9 kg. Keyword: grow-out, barramundi, floating net cages Abstrak Budidaya ikan kakap putih (Lates calcarifer) adalah salah satu usaha perikanan air tawar yang memiliki prospek cerah untuk dikembangkan dengan harga jual yang mencapai Rp 75.000 per kilogram. Berdasarkan data permintaan dari Kementerian Kelautan dan Perikanan RI tahun 2020, permintaan mencapai 522.267 ton, sedangkan produksi hanya 492.267 ton. Permintaan yang lebih tinggi daripada produksi menunjukkan bahwa ikan kakap putih memiliki potensi besar untuk dikembangkan lebih lanjut. Budidaya laut yang populer untuk dikembangkan adalah penggunaan keramba jaring apung (KJA). Tujuan dari dilaksanakannya penelitian ini untuk menganalisis mengenai teknik pembesaran ikan kakap putih (Lates calcarifer) menggunakan KJA kotak di Balai Besar Riset Budidaya Laut dan Penyuluhan Perikanan Gondol, Bali. Teknik pengambilan data yang digunakan dalam PKL yaitu secara primer dan sekunder. Kegiatan yang dilakukan dalam usaha pembesaran ikan kakap putih menggunakan media KJA kotak meliputi persiapan kolam, penebaran benih, manajemen pakan, manajemen kualitas air, manajemen kesehatan ikan, kegiatan panen dan pasca panen. Total benih ikan kakap putih yang ditebar di KJA kotak BBRBLPP Gondol sebanyak 20.900. Jenis-jenis KJA kotak yang ada di BBRBLPP Gondol ada dua yaitu KJA kayu dan KJA HDPE. Ukuran-ukuran KJA kotak yang ada di BBRBLPP Gondol terbagi menjadi 4 yaitu 2x2x2 meter, 3x3x3 meter, 4x4x4 meter dan 2x4x4 meter. Produktivitas pembesaran ikan kakap putih selama 30 hari yaitu SGR 0,83%. SR 92,1%; 96,2% dan 98,9% serta FCR sebesar 0,654. Produksi total pada akhir masa pemeliharaan sebesar 573,9 kg. Kata kunci: pembesaran, kakap putih, keramba jaring apung